If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2p = 4 + 3p Solving 5 + -2p = 4 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 5 + -2p + -3p = 4 + 3p + -3p Combine like terms: -2p + -3p = -5p 5 + -5p = 4 + 3p + -3p Combine like terms: 3p + -3p = 0 5 + -5p = 4 + 0 5 + -5p = 4 Add '-5' to each side of the equation. 5 + -5 + -5p = 4 + -5 Combine like terms: 5 + -5 = 0 0 + -5p = 4 + -5 -5p = 4 + -5 Combine like terms: 4 + -5 = -1 -5p = -1 Divide each side by '-5'. p = 0.2 Simplifying p = 0.2
| 5x-(2-3x)=4x+6 | | 10x^2+2x=6 | | 34-9x=-11x-46 | | -7x+2=-12+7x | | 594=174-15x | | 5m+6=10whatism | | 5m+6=10 | | -3x-188=-16x+384 | | 5x-3=25+x | | 173-11x=-5x-217 | | 7+4x=2x+3 | | -2sin^2x+3sinx-1=0 | | (4+3i)(5-6i)= | | -70-17x=60-15x | | 146=18.30 | | -7x-10=4x+111 | | 293=-3x-4(-5x-35) | | X+15-2x=x+x-15 | | 20=2XW | | -99=293-14x | | 2n^2-2n-20=0 | | 7=2(3x-5)-4(x-6) | | 4x+15=x+84 | | y=-5x^2+22x-8 | | F+4=4f-5 | | 6/5-9/4 | | 4x^4-3x^3+2x^2-1=0 | | 5x+3=-4x+30 | | 4x^4-3x^3+2x^2-1=y | | 6x-3(x-1)= | | 4x^3-4x-9=0 | | 2X^4-10X^2+11=0 |